2018
DOI: 10.1038/s41388-018-0438-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of PIP5K1α/pAKT and targeted inhibition of growth of subtypes of breast cancer using PIP5K1α inhibitor

Abstract: Despite recent improvement in adjuvant therapies, triple-negative, and ER subtypes of breast cancer (BC) with metastatic potentials remain the leading cause of BC-related deaths. We investigated the role of phosphatidylinositol-4-phosphate 5-kinase alpha (PIP5Kα), a key upstream factor of PI3K/AKT, and the therapeutic effect of PIP5Kα inhibitor on subtypes of BC. The clinical importance of PIP5K1α and its association with survivals were analyzed using three BC cohorts from Nottingham (n = 913), KM plotter (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
1
30
0
2
Order By: Relevance
“…Importantly, subsequent removal of Akt inhibition restored podosome levels to control (Figure S3G). Recently, a phosphorylated Akt signal was detected at invadopodia (Sarwar et al., 2019); using the same antibody, we detected phosphorylated Akt within the podosome (Figure 3I). We do not detect a direct interaction between PAK4 and Akt; we would, therefore, suggest that an important role of PAK4 in podosome formation is the activation of the Akt pathway but not by direct phosphorylation of Akt.…”
Section: Resultssupporting
confidence: 54%
“…Importantly, subsequent removal of Akt inhibition restored podosome levels to control (Figure S3G). Recently, a phosphorylated Akt signal was detected at invadopodia (Sarwar et al., 2019); using the same antibody, we detected phosphorylated Akt within the podosome (Figure 3I). We do not detect a direct interaction between PAK4 and Akt; we would, therefore, suggest that an important role of PAK4 in podosome formation is the activation of the Akt pathway but not by direct phosphorylation of Akt.…”
Section: Resultssupporting
confidence: 54%
“…As an example, PIP5K1α is overexpressed in prostate cancer and is a poor prognostic indicator for this disease (283)(284)(285). Moreover, ISA-2011B -a small molecule inhibitor of PIP5K1α, is an effective anti-cancer agent in both prostate (285) and triple-negative breast cancer models (286). However, PIP5K1α has oncogenic functions outside of Golgi trafficking including the regulation of p53 oncoprotein stability in the nucleus (287) and KRAS signalling (288).…”
Section: Pip5k1α − a Pi4p 5-kinase With Links To Golgi Exit And Cancermentioning
confidence: 99%
“…Our present study suggests that tumor-infiltrating cells are likely to be one of the major sources of the increased PIP5K1α and AKT activity observed in PCa. We have previously shown that the overexpression of PIP5K1α signaling resulted in aggressive tumor progression in several mouse models [ 16 , 18 , 26 ]. In this study, we found that PIP5K1α was highly expressed in PCa cells but was undetectable in bone marrow cells and the U-937 myeloid cell line.…”
Section: Discussionmentioning
confidence: 99%